Gender gaps and the structure of local labor markets - Barbara Petrongolo; Maddalena Ronchi (Queen Mary University of London, School of Economics and Finance, 2020)
In this paper we discuss some strands of the recent literature on the evolution of gender gaps and their driving forces. We will revisit key stylized facts about gender gaps in employment and wages in a few high-income countries. We then discuss and build on one gender-neutral force behind the rise in female employment, namely the rise of the service economy, which is also closely related to the polarization of female employment and to the geographic distribution of jobs, which is expected to be espe- cially relevant for female employment prospects. We finally turn to currently debated causes of remaining gender gaps and discuss existing evidence on labor market con- sequences of women's heavier caring responsibilities in the household. In particular, we highlight how women's stronger distaste for commuting time may feed into gender pay gaps by making women more willing to trade off steeper wage gains for shorter commutes.
Keywords: J16; J21; J31; J61; 330; gender gaps; industry structure; local labor markets